Can starling eggs be useful as a biomonitoring tool to study organohalogenated contaminants on a worldwide scale? - Marcel Eens; Veerle L.B. Jaspers; Evi Van den Steen; Melissa Bateson; Claudio Carere; Philippe Clergeau; David Costantini; Zdravko Dolenec; John E. Elliott; John Flux; Helga Gwinner; Richard S. Halbrook; et al. (Environment International, 2013)
Large-scale international monitoring studies are important to assess emission patterns and environmental distributions of organohalogenated contaminants (OHCs) on a worldwide scale. In this study, the presence of OHCs was investigated on three continents (Europe, North America and Australasia), using eggs of starlings (Sturnus vulgaris and Sturnus unicolor) to assess their suitability for large-scale monitoring studies. To the best of our knowledge, this is the first study using bird eggs of the same species as a biomonitor for OHCs on an intercontinental scale. We found significant differences in OHC concentrations of the eggs among sampling locations, except for hexachlorocyclohexanes (HCHs). Mean concentrations of sum polychlorinated biphenyls (PCBs) in eggs ranged from 78±26 ng/g lipid weight (lw) in Australia to 2900±1300 ng/g lw in the United States. The PCB profile was dominated by CB 153 and CB 138 in all locations, except for New Zealand, where the contribution of CB 95, CB 101 and CB 149 was also high. The highest mean sum polybrominated diphenyl ether (PBDE) concentrations were found in Canada (4400±830 ng/g lw), while the lowest mean PBDE concentrations were measured in Spain (3.7±0.1 ng/g lw). The PBDE profile in starling eggs was dominated by BDE 47 and BDE 99 in all countries, but in Belgium, the higher brominated PBDEs had a higher contribution compared to other countries. For the organochlorine pesticides (OCPs), dichlorodiphenyltrichloroethanes (DDTs) ranged from 110±16 ng/g lw in France to 17,000±3400 ng/g lw in New Zealand, while HCHs and hexachlorobenzene were generally in low concentrations in all sampling locations. Chlordanes were remarkably high in eggs from the United States (2500±1300 ng/g lw). The OCP profile in all countries was largely dominated by p,p′-DDE. In general, the worldwide trends we observed in starling eggs were in accordance with the literature on human and environmental OHC data, which suggests that there is potential for using starling eggs as a biomonitoring tool on a large geographical scale. Keywords: Polychlorinated biphenyls, Polybrominated diphenyl ethers, Organochlorine pesticides, Biomonitoring, Sturnus, Birds